Tränare, domare och styrelseledamöter : Kvinnors historiska förutsättningar inom basketens bestämmande organ - Setzman, Elin (Luleå tekniska universitet, Institutionen för ekonomi, teknik och samhälle, 2020)
In this essay I have researched different prerequisites for women to engage as coaches, referees or board members within basketball in Luleå between the years 1969 to 1989. The different prerequisites that have been analyzed are economic and social and possibilities for competence development. To find answers for this I have researched change in gender balance in board meetings and among coaches but also how questions about equality have been discussed in meetings and if actions have been made to include more women. The prime material has been protocols from board meetings and movement stories from The Basketball Association of Norrbotten and Gammelstads Basketball Club. The content in these have been connected to national guidelines that was formed by the National Sports Association during the twenty years that the essay is limited to. The result shows that it has been difficult for women to take place within decision makings in basketball. Most board members, coaches and referees have often been men and the underrepresentation of women was not presented as a problem in the beginning. Even when women have taken place in boards and have started to work more actively with equality, the formulation of problems have often considered women to be the reason that there is inequality. Despite the problems, basketball in Luleå has achieved a more even gender balance in boards compared to sports on a national level. On the other hand, inequality is still a fact on the coaching side.